Go home! : the true story of James the cat - Meggs, Libby Phillips (Morton Grove, Ill. : A. Whitman, 2000)
A homeless cat spends several seasons trying to survive the elements until at last a suburban family adopts him.
Keywords: Cats -- Juvenile fiction; Cats -- Fiction; Lost and found possessions -- Fiction